Investigation of the Effect of Heating Duration in Gambier (Uncaria gambir Roxb.) Processing on Its Phytochemical Composition and the Resulting Characteristics of a Gambier-based Acne Balm Product - Rilvi Muhammad Tio; Najla Rosyadah; Novizar Novizar; Rini Rini; Tuty Anggraini; Umar Ahmed; Cesar Welya Refdi; Daimon Syukri (Journal of Applied Agricultural Science and Technology, 2025)
Gambier (Uncaria gambir Roxb.) contains potent bioactive compounds with strong natural antimicrobial properties, making it a promising ingredient for acne treatment. However, its application in topical formulations remains limited due to a lack of understanding regarding the impact of processing conditions, particularly heating, on its functional efficacy. This study investigated the effect of heating duration on the characteristics of an acne treatment balm formulated with black cube gambier. Experiments using a completely randomized design (CRD) were carried out for 0, 30, 60, 90, and 120 minutes of heating durations to evaluate the balm's physical, chemical, and microbial properties. The results demonstrate that heating duration significantly influenced key parameters, including homogeneity, spreadability, melting point, irritation potential, texture, color, pH, total phenol content, and antibacterial activity (p < 0.05). The most optimal results were obtained at 120 minutes, yielding a balm with superior homogeneity, spreadability (4.47 cm), melting point (50°C), pH (7.44), total phenol content (54.28%), and diameter of the inhibition zone (16.35 mm). FTIR analysis confirmed an increase in phenolic compound stability, indicating enhanced antibacterial potential. These findings suggest that extended heating duration improves the stability and performance of gambier-based formulations. The optimized acne balm formulation highlights the potential of locally sourced gambier as a natural, eco-friendly acne treatment. Further research is recommended to evaluate product shelf-life, consumer acceptability, and industrial scalability.